THE INFLUENCE OF ORGANIZATIONAL CULTURE, MOTIVATION, AND WORK DISCIPLINE ON EMPLOYEE PERFORMANCE DURING THE COVID-19 PANDEMIC IN PT. SARANA TITIAN PERMATA 1 - Rustam, Rustam; Sawitri, Dyah; Orbaningsih, Dwi (Jurnal Ekonomi Balance, 2021)
In the era of globalization, competition between companies is getting sharper, so it requires companies to always be the best. The increasingly fierce competition also shapes the development of increasingly increasing technology and information, resulting in global and comprehensive competition. Therefore, we need workers who really want to work and are able to survive in oil palm plantations. This study aims to determine (1) Does Organizational Culture partially affect the performance of employees at PT. Sarana Titian Permata 1, (2) Does motivation partially affect the performance of employees at PT. Sarana Titian Permata 1, (3) Does Work Discipline partially affect employee performance at PT. Sarana Titian Permata 1. The method of collecting data is through questionnaires distributed to employees of PT. Sarana Titian Permata 1. The samples taken were 54 respondents using the saturated sample technique. The data obtained were then processed using a computer software analysis tool, namely SPSS version 23. This analysis includes validity test, reliability test, multiple regression analysis test, classical assumption test, and statistical test through t statistical test, F statistical test, and the coefficient of determination (R2 ). The results of the t-statistical test indicate that Organizational Culture has a positive and significant effect on employee performance with a significance (Sig.) of 0.000 less than 0.05 (α), then motivation has a positive and significant effect on employee performance with a significance (Sig.) of 0.023. smaller than the value (α) of 0.05, while Work Discipline has no significant effect on employee performance with a significance (Sig.) of 0.547 greater than the value (α) of 0.05. Then the F statistic test and the coefficient of determination (R2) show that organizational culture, motivation and work environment simultaneously affect employee performance with a contribution of 69.7%. While the remaining 30.3% is explained by other independent variables that are not included in the analytical model of this study.